Room temperature plasmon-enhanced InAs0.91Sb0.09-based heterojunction n-i-p mid-wave infrared photodetector - Tobing, Landobasa Yosef Mario (2019)
Middle wavelength infrared (MWIR) photodetectors have a wide range of applications, but almost all of them operate at low temperature due to the limit of materials and device structures. The capability of plasmonic structures to localize electromagnetic wave on the deep subwavelength scale provides the possibility for MWIR photodetectors operating at room temperature. Here, we report a high sensitivity room temperature MWIR photodetector which is an InAs0.91Sb0.09-based heterojunction n-i-p photodiode integrated with a Au-based two-dimensional subwavelength hole array (2DSHA). A room temperature detectivity of 0.8 × 1010 cm Hz1/2 W−1 and a response time of 600 ns are achieved. The non-cooling high performance of 2DSHA-InAs0.91Sb0.09 based heterojunction photodetectors will make their applications easier, broader, and economic.